Quantitative flow ratio to predict non-target-vessel-related events at 5 years in STEMI patients undergoing angiography-guided revascularization. (25th November 2020) - Baer, S; Kavaliauskaite, R; Ueki, Y; Otsuka, T; Engstrom, T; Baumbach, A; Roffi, M; Von Birgelen, C; Vukcevic, V; Pedrazzini, G; Kornowski, R; Tueller, D; et al.
Abstract: Background: In patients with ST-segment-elevation myocardial infarction (STEMI), angiography-based complete revascularization is associated with superior outcomes compared with culprit-lesion-only percutaneous coronary intervention (PCI). Quantitative Flow Ratio (QFR) is a novel, non-invasive, vasodilator-free method to assess the hemodynamic significance of coronary stenoses. Purpose: To investigate the incremental value of QFR over angiography alone in the assessment of non-culprit lesions (NCL) in STEMI patients undergoing primary PCI. Methods: In the randomized, multicenter COMFORTABLE AMI trial, STEMI patients underwent angiography-guided complete revascularization. QFR was determined in untreated non-target vessels by assessors blinded for clinical outcomes. Results: Out of 1161 STEMI patients, 946 vessels in 617 patients could be analyzed by QFR. At 5-year follow-up, the rate of the primary endpoint cardiac death, non-target vessel myocardial infarction (non-TV-MI) and clinically indicated, non-target vessel revascularization (non-TVR) was significantly higher in patients with QFR ≤0.80 compared with QFR >0.80 (62.9% vs. 12.7%, HR 7.20, 95% CI 4.46–11.62, p<0.001), driven by higher rates of non-TV-MI (15.4% vs. 3.6%, HR 4.59, 95% CI 1.72–12.23, p=0.002) and non-TVR (58.6% vs. 7.7%, HR 10.99, 95% CI 6.39–18.91, p<0.001). No significant differences for cardiac death were observed. Multivariate analysis identified QFR ≤0.80, MI SYNTAX score and left ventricular function as independent predictors of the primary endpoint. QFR ≤0.80 showed an accuracy of 86.1%, sensitivity of 23.2%, specificity of 97.5%, positive predictive value of 62.9% and negative predictive value of 87.5% for the prediction of the primary endpoint. Conclusions: Our study results suggest incremental value of QFR over angiography-guided PCI for NCL among STEMI patients undergoing primary PCI. Funding Acknowledgement: Type of funding source: None